Deviasi Sosial di Era Digital: Analisis Relasi antara Kepentingan Eksistensi Individu dan Tuntutan Norma Masyarakat pada Perilaku Cyberbullying Remaja - Lubis, Avicenna (Journal of Society Bridge, 2026)
This study examines adolescent social deviation on social media arising from conflicts between individual interests in digital validation and societal normative demands. Research variables include social validation needs, weakened social control, platform algorithm influence, and deviant behaviors such as cyberbullying and misinformation. The study aims to analyze psychosocial and structural drivers of noncompliance with social norms and legal regulations, and to assess the effectiveness of conventional social control. Using a qualitative library research approach, data were collected from indexed academic journals, official institutional reports, cyber law regulations, and credible mass media sources published between 2020 and 2025. Data were analyzed through qualitative content and thematic analysis, drawing on Anomie Theory, Social Control Theory, and the Online Disinhibition Effect. Findings indicate that attention-seeking motives, cyberspace anonymity, and algorithmic logics normalize deviant behavior among adolescents. The study concludes that mitigating digital social deviation requires strengthening digital empathy and systemic collaboration among families, educational institutions, policymakers, and platform providers